Developing a feed barley with more balanced aminoacid composition - Lange M.; Vincze E.; Wieser H.; Holm P. (Cereal science and technology for feeding ten billion people: genomics era and beyond, 2008)
In this study we report the selective suppression of the synthesis of C-hordeins in barley by antisense technology. We found a reduction in the total hordein content, especially in the C-hordeins, and increases in the glutelin fraction. Amino acid analyses revealed reductions in the contents of proline, glutamic acid/glutamine and phenylalanine while the levels of all other amino acids were increased. We conclude that antisense-mediated suppression of C-hordein synthesis may be a promising approach for improving the nutritional value of barley as a feed crop while at the same time reducing the environmental nitrogen load.
Meeting of the Eucarpia Cereal Section, 2006/11/13-17, Lleida (Spain)